A SYSTEMATIC LITERATURE REVIEW ON THE IMPACT OF INCLUSIVE MANAGEMENT ON ORGANIZATIONAL PERFORMANCE THROUGH EMPLOYEE ENGAGEMENT - Ranny Fitria Puspitasari; Budi Eko Soetjipto; Ludi Wisnu Wardhana (RADJA PUBLIKA, 2025)
This study systematically reviews 71 scholarly articles from the past five years in the Scopus database (Q1–Q4) that examine the relationship between inclusive management—which includes diversity management, equality policies, and inclusion initiatives—and organizational performance, with employee engagement as a mediating variable. Using a Systematic Literature Review approach and thematic analysis, the findings reveal that DEI (diversity, equity, inclusion) practices significantly enhance organizational effectiveness, efficiency, innovation, and sustainability. Diversity management strengthens decision-making and innovation; equality policies promote accountable governance and distributive justice; and inclusion initiatives foster collective participation and employee loyalty. Employee engagement serves as a mediating factor linking DEI practices to performance at both individual and institutional levels. The study develops an integrative conceptual model and identifies directions for future research, including contextual frameworks and longitudinal approaches. These insights offer a strategic foundation for formulating inclusive, equitable, and sustainable management policies.